Comparison of Wave Amplitude, Implicit Time and Comfort Level Using Dawson-Trick-Litzkow, Jet and Dencott Electrodes in Electroretinography in Normal Adults - Theresia Yinski Pistari Gondosari; Mohamad Sidik; Syntia Nusanti (Indonesian Vitreoretinal Society, 2020)
Introduction: Several electrodes can be used in standard full-field electroretinography (ERG). However, there are no standard values for Indonesians yet. Therefore, this research aims to establish normal values, to compare them and to compare comfort levels using DTL, Dencott and Jet electrodes in Indonesian adults. Method: Through convenient sampling, 58 normal Indonesian subjects, age 19-49 years old were selected. ERG amplitudes and implicit time values were measured according to recommendations by the International Society for Clinical Electrophysiology of Vision (ISCEV). Evaluations consisted of scotopic 0.01, 3.0, OP and photopic 3.0 flicker. After examination, all subjects filled in a questionnaire about comfort levels, adopted from the visual analog scale. Result: We observed a statistically significant difference in ERG normal values between electrodes with higher wave amplitudes and longer implicit times in Dencott and jet electrodes, compared to DTL electrodes. Jet and DTL electrodes are more comfortable than Dencott electrodes for Indonesian adults in standard full-field electroretinography. Conclusion: DTL electrodes give the lowest wave amplitudes and the shortest implicit times and are the most comfortable electrode compared to Dencott and ERG jet electrodes, in standard full-field electroretinography in Indonesian adults.